2020
DOI: 10.3390/diagnostics10110875
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Coronary Artery Disease by Micro-RNA Analysis in Asymptomatic Patients Stratified by Coronary CT Angiography

Abstract: Early detection of asymptomatic coronary artery disease (CAD) is essential but underdeveloped. The aim of this study was to assess micro-RNA (miRNA) expression profiles in patients with or without CAD as selected by coronary CT angiography (CTA) and stratified by risk of CAD as determined by Framingham Risk Score (FRS). In this pilot study, patients were divided into two groups based on the presence or absence of CAD. Disease status was determined by Coronary CTA by identification of atherosclerosis and/or cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…It is possible that deviations in the levels of this miRNA, along with miR-141-3p, can be used as a marker of the stability of atherosclerotic lesions. An atheroprotective role of miR-181b-5p is also suggested in a Patterson et al’s study, where they analyzed a large pool of miRNAs expression using the pathway-specific microarray profiling [ 38 ]. The expression of this miRNA was higher in patients with coronary atherosclerosis and a low risk of CVC, according to the Framingham score.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that deviations in the levels of this miRNA, along with miR-141-3p, can be used as a marker of the stability of atherosclerotic lesions. An atheroprotective role of miR-181b-5p is also suggested in a Patterson et al’s study, where they analyzed a large pool of miRNAs expression using the pathway-specific microarray profiling [ 38 ]. The expression of this miRNA was higher in patients with coronary atherosclerosis and a low risk of CVC, according to the Framingham score.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-155 is known to be implicated in inflammatory responses where it strengthen inflammation and sustain macrophages [ 61 , 62 ]. Finally, Patterson et al showed downregulation of miR-133a and 208a in CAD patients [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs circulate throughout the body, interacting with tissues and organs [37]. For example, hsa-let-7f-5p, hsa-miR-28-5p, hsa-miR-320d, and hsa-miR-99a-5p were found in blood in inflammatory states [38][39][40][41]. The expression of certain miRNAs may be associated with inflammation and periodontitis.…”
Section: Discussionmentioning
confidence: 99%